Microplastics in rice: a systematic review - Iva Ferreira-Marques; Sara A. M. Silva; Joana C. Prata (RevSALUS, 2025)
The recognition of the omnipresence of microplastics (MPs), plastic particles <5 mm, has raised concerns over the potential for adverse health effects. They are found in common basic foods, such as rice, water, vegetables, and fish, yet their toxicity potential and impacts on human health remain poorly understood. To date, MPs and associated contaminants (e.g., plastic additives) are suspected of contributing to chronic inflammation, autoimmune diseases, endocrine disruption, and increased cancer risk [1].  Although MPs have been studied in marine environments and certain food sources, data on their contamination in daily-consumed cereals, such as rice, are scarce. What effects might MPs have on the food itself? MPs can transport pathogenic agents, facilitating food contamination [2], and can act as vectors for pesticides and heavy metals, increasing exposure risk [3]. The few existing studies vary in their quantification and characterization methods for MPs, limiting the comparability. Yet, determining concentration of MPs in foods is critical to estimate human exposure and conduct risk assessment. The purpose of this systematic review is to assess the presence of MPs in rice, one of the most consumed foods globally. We analyzed the origins of the rice, the concentrations of MPs found, and their characteristics, such as color, shape, polymer types, and sizes, as well as the methods used to extract, identify, characterize, and quantify MPs. This review was conducted through a search on three databases—Clarivate (Web of Science), Scopus, and Google Scholar—on November 8th, 2024, using the keywords “(rice OR oryza sativa) AND (microplastics OR plastic AND particles OR microplastic)”, retrieving five documents. In the selected studies, various analytical methods were used to identify MPs, including pyrolysis-gas chromatography-mass spectrometry (Pyr-GC-MS), microscopy, Raman micro-spectroscopy, and hyperspectral imaging. Sample preparation involved different digestion protocols, such as the use of 65-68% nitric acid combined with 30% hydrogen peroxide (in a 4:1 v/v ratio at 50°C) or 65% nitric acid at 60°C for 18 hours, as well as liquid-liquid extraction techniques. The studies reviewed reported MP concentrations of 2.8 mg/100g in washed rice and 3.7 mg/100g in unwashed rice. For cooked rice, the concentration was 5 MPs/kg. In take-out rice, concentrations of 1500 MPs/kg were found. The analyzed rice packaging showed an average of 0.243 MPs/cm². The most frequently detected polymer types were polyethylene (PE) and polyethylene terephthalate (PET). Microplastic contamination in rice is influenced by production, packaging, and transportation. Packaging, especially during friction and cooking, significantly contributes to contamination. Washing rice before cooking reduces microplastic concentrations, though its effectiveness varies. Detection methods, such as µ-Raman spectroscopy, are common, but strong digestion solutions like 65% HNO₃ may degrade microplastics, leading to underestimation. There is a pressing need for more comprehensive studies to better understand the contamination pathways and improve statistical data on MP contamination in staple foods. This is essential to ensure food safety and develop effective mitigation strategies.